THE AVAILABILITY OF INDONESIAN OIL PRODUCT THAT IS USED IN THE UPGRADED BROWN COAL PROCESS - Iwan Rijwan; BUKIN DAULAY; Gandhi Kurnia Hudaya (Puslitbang tekMIRA, 2008)
Indonesian coal has a potential to be a major future primary energy source due to its large resource, easy and low cost of exploitation, good quality and supported by appropriate infrastructure. However, more than 65% of the coal resources are categorized as LRC and this type of coal needs to be upgraded before it is used and transported for a long distance. One of the upgrading processes is UBC. Kerosene, LSWR and spray oils are used for UBC process as heating media, material for closing coal pores and oil for briquette machine, respectively. The specification and price of kerosene in Indonesia which is used for both household and industries are controlled by PT PERTAMINA. However in the case of LSWR, PT PERTAMINA does not control the quality and the price. Therefore in the market there are different of qualities and prices of LSWR. All oil refineries belong to PT PERTAMINA produces LSWR and kerosene. They guarantee the con- tinuity of oil supply to customer. They recommend to utilize a heavy aromatic for kerosene substitu- tion and asphalt and decant oil to substitute LSWR. The oil will be transported to the UBC plant from the nearest oil refinery using lorries or tankers transportation agency that is recommended by PT PERTAMINA.